2020
DOI: 10.21448/ijsm.581500
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antibacterial and Antifungal Activities of Different Extracts of Silybum marianum Collected from Duhok (Iraq)

Abstract: In this study, antioxidant, antibacterial and antifungal activities of Silybum marianum (L.) Gaertn. collected from Duhok (Iraq) were determined. Ethanol, methanol and dichloromethane extracts of the fruit part of plant were obtained. Antioxidant potential was determined with TAS and TOS kits using ethanol extracts. Antibacterial and antifungal activity were determined using agar dilution method. Antibacterial activity was determined against 6 bacterial strains (Staphylococcus aureus, S. aureus MRSA, Enterococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
5
22
0
1
Order By: Relevance
“…There are numerous methods developed for the assessment of antioxidant activities of various materials (Sevindik et al, 2017;Mohammed et al, 2019). The outcomes of the methods based on the deactivation of radicals, such as DPPH and ABTS, differ inside reactions appearance and reaction kinetics (Layina-Pathirana et al, 2006;Mareček et al, 2017).…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous methods developed for the assessment of antioxidant activities of various materials (Sevindik et al, 2017;Mohammed et al, 2019). The outcomes of the methods based on the deactivation of radicals, such as DPPH and ABTS, differ inside reactions appearance and reaction kinetics (Layina-Pathirana et al, 2006;Mareček et al, 2017).…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…It is noted that the presence of sufficient amount of acid is essential to obtain high quality vinegars (Giudici et al, 2017). Different plant species and products are used in the treatment of diseases in many parts of the world (Sevindik et al, 2017;Mohammed et al, 2019;Pehlivan et al, 2018;Mohammed et al, 2020). Vinegar has long been used in both natural folk medicine and traditional medicine for treating a variety of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the results of the antimicrobial activity of silymarin correlated with the findings of Mojgan and Roya (2016), who reported no significant effect on Gr (-) bacteria. Mohammed et al (2019) reported that antibacterial effects of S. marianum extracts were higher than antifungal effects and ethanol extracts have higher antimicrobial activity than methanol extracts. Unlike the results of our study, plant extracts have a higher antimicrobial effect against Gr (-) bacteria (Mohammed et al, 2019).…”
Section: Determination Of Antimicrobial Activity In Seed Oil and Silymentioning
confidence: 99%
“…Mohammed et al (2019) reported that antibacterial effects of S. marianum extracts were higher than antifungal effects and ethanol extracts have higher antimicrobial activity than methanol extracts. Unlike the results of our study, plant extracts have a higher antimicrobial effect against Gr (-) bacteria (Mohammed et al, 2019). Similarly, neither silymarin nor seed oil has antifungal activity.…”
Section: Determination Of Antimicrobial Activity In Seed Oil and Silymentioning
confidence: 99%
“…From all over the world billions of almost 1.5 situations of the run is happing every year, dominantly in the creations of nations, to have a sudden look upon almost 3 million of children aging 5 years. World Health Organisation (WHO) has assessed that 70% of dysentery scenes are caused by naturally defiled nourishment (Goldsteen et al, 2014;Mohammed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%